Reproductive Health and Rights The Perception of Selected Maranao Men - Jumadla, Doreen G.; Magno, Jenny Celina L.; Lastimosa, Mary Joy E.; Castro, Luz C. Sevidal (2010)
This is a case study of the perception of some Maranao men in Barangay

Bonbonon, Iligan City, about the reproductive health and rights of their wives Qualitative in design, it pioneers the search for information on the topic from men belonging to a cultural community.

This study attempts to answer the following questions:

1. Are the Maranao men aware of their wives' reproductive health and reproductive rights? 2. What is the Maranao men's perception of their role in deciding about family size?
3. What is their role in deciding about the spacing and timing of their children?
4. What are the men doing to ensure the enjoyment by their wives of their reproductive health rights?

The study discusses the services that contribute to their wives' well-being by preventing reproductive health problems. It tackles the following reproductive nights 1) the right to health care and health protection; and 2) the right to decide whether and when to have children.
Keywords: Reproductive health -- Social aspects; Reproductive rights